2023
DOI: 10.1038/s41598-023-37624-w
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and phonemic processing are impaired in individuals with aphasia

Abstract: Acoustic and phonemic processing are understudied in aphasia, a language disorder that can affect different levels and modalities of language processing. For successful speech comprehension, processing of the speech envelope is necessary, which relates to amplitude changes over time (e.g., the rise times). Moreover, to identify speech sounds (i.e., phonemes), efficient processing of spectro-temporal changes as reflected in formant transitions is essential. Given the underrepresentation of aphasia studies on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
2
6
0
Order By: Relevance
“…This would mean that IWA also show impaired processing of speech acoustics. This is in line with findings from Kries et al (2023), who found that 76% of IWA had a low-level acoustic or phonemic processing impairment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This would mean that IWA also show impaired processing of speech acoustics. This is in line with findings from Kries et al (2023), who found that 76% of IWA had a low-level acoustic or phonemic processing impairment.…”
Section: Discussionsupporting
confidence: 92%
“…The target age of healthy controls was gradually adapted based on the mean age of IWA included in the study (supplementary figure S.2). The participants in this study are partly overlapping with participants in Kries et al (2023).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…All aphasia participants were tested in the chronic phase after stroke (time since stroke onset in months median [range]: 16.1 [6–126.1]). The aphasia sample was checked for language impairments at the moment of data collection using two standardized diagnostic aphasia tests, that is, the diagnostic test ScreeLing Visch‐Brink et al ( 2010 ) and the Dutch picture‐naming test (Nederlandse Benoemtest [NBT]; Van Ewijk et al, 2020 , using the same procedure as reported in Kries et al, 2023 ). The ScreeLing was administered on a tablet using the Gorilla Experiment Builder ( http://www.gorilla.sc ; Anwyl‐Irvine et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…[25] Phonology is also defined as the science that studies functional sounds in certain language structures in terms of their nature, quality, and semantic function, or in other words the science that studies the function of semantic sounds in a word and sentence structure in a language. [26] Knowledge of modern linguistics is what helps us to interpret the causes of some sounds or all of them so that they can become a decree without change. In modern linguistic science, the sounds of language are closely related to acoustic equivalence phonetics ( ‫األكوستيكي‬ ‫]72[.…”
Section: Qur'anic Phonology and Modern Linguisticsmentioning
confidence: 99%